SHARIA COMPLIANCE IMPLEMENTATION IN ISLAMIC BANKING: A STUDY ON BUILDING CUSTOMER CONFIDENCE - Lahuri, Setiawan Bin; Prastyaningsih, Ika; Mahfudz, Akhmad Affandi; Ahmad, Rusyda Afifah; Muhammad, Izlawanie (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
The lack of customer trust in Islamic banks has led to in a persistently low market share of the Islamic financial market in Indonesia, which is currently below 5.33%. Therefore, this study aims to investigate the implementation of Sharia compliance in Indonesian Sharia Banks, with a particular emphasis on social performance. The qualitative methods and Analysis Network Process (ANP) were used to investigate this phenomenon, with data collected from banking compliance officers, staff, and Sharia compliance experts. The results of this study show that Bank Syariah Indonesia Solo Branch has successfully implemented Sharia compliance across 42 items comprising 6 indicators of the Islamic Social Reporting Index. This comprehensive method is evident in the bank's focus on operations, products, and employees, showing a holisitic commitment to Sharia compliance in Islamic banking.